A158 THE WAITING GAME: A SYSTEMATIC REVIEW OF ACCESS TO INFLAMMATORY BOWEL DISEASE CARE AND ITS IMPACT ON PATIENT OUTCOMES IN CANADA AND NOVA SCOTIA. (1st March 2018) - Mathias, H; Jones, J
Abstract: Background: Inflammatory Bowel Disease (IBD), including Crohn's Disease (CD) and Ulcerative Colitis (UC), is a chronic early onset disease with debilitating lifelong effects on patients' physical and mental health. IBD is also associated with significant financial and social ramifications. Canada is reported as having the highest prevalence rate of IBD in the world. Within Canada, the province of Nova Scotia (NS) has the highest incidence rates of IBD. Appropriate access to timely and quality care is essential for disease management but very little is known about the impact of access to IBD care on disease related outcomes. Aims: How does access to IBD care inform patient outcomes in Canada, and more specifically, in Nova Scotia? Methods: A systematic review of literature pertaining to access to IBD care in Canada was conducted in July 2016. Summon and NovaNet databases were used in conjunction with an internet search engine being used to find relevant gray literature. The search terms "Access" + "Care" + "IBD" + "Canada" + "Nova Scotia" were used. Results were refined for "full texts online" and limited to peer reviewed journals published in English between 2006 and 2016. Search results were sorted by relevance. Exclusion criteria were articles not focused on both IBD and Nova Scotia. A secondary search was conducted using Novanet using the search terms "IBD" + "Nova Scotia." Results: After the initial search, Summon produced 19 results, while Novanet could not find any matching results. After screening, only 2 results were included in the synthesis (Figure 1). The secondary search yielded 2 articles; however, after screening, none of the articles were included. Included articles and relevant grey literature were analyzed using the patient-centered Five 'A's of Access framework (approachability, acceptability, availability & accommodation, affordability and appropriateness) created by Levesque, Harris and Russell (2013). Conclusions: Despite an increasing focus on access to health care and patient-centered evidence based medicine, and a notably high incidence rate of IBD in Nova Scotia, this systematic review uncovered large gaps in literature concerning access to IBD care in Canada and Nova Scotia. While some innovative work is being done in the province to address issues of access, the lack of available research in the field of IBD means that actual and perceived access is not adequately understood. Increased patient-centered research in the field of IBD would benefit the availability of accessible patient-centered care through evidence-based systems planning. Funding Agencies: None